Predation of Ladybird Beetles (Coleoptera: Coccinellidae) by Amphibians - John J. Sloggett (Insects, 2012)
Studies of predation of ladybird beetles (Coccinellidae) have focused on a limited number of predator taxa, such as birds and ants, while other potential predators have received limited attention. I here consider amphibians as predators of ladybirds. Published amphibian gut analyses show that ladybirds are quite often eaten by frogs and toads (Anura), with recorded frequencies reaching up to 15% of dietary items. Salamanders (Caudata) eat ladybirds less frequently, probably as their habits less often bring them into contact with the beetles. Amphibians do not appear to be deleteriously affected by the potentially toxic alkaloids that ladybirds possess. Amphibians, especially frogs and toads, use primarily prey movement as a release cue to attack their food; it is thus likely that their ability to discriminate against ladybirds and other chemically defended prey is limited. Because of this poor discriminatory power, amphibians have apparently evolved non-specific resistance to prey defensive chemicals, including ladybird alkaloids. Although amphibian-related ladybird mortality is limited, in certain habitats it could outweigh mortality from more frequently studied predators, notably birds. The gut analyses from the herpetological literature used in this study, suggest that in studying predation of insects, entomologists should consider specialized literature on other animal groups.